Information theoretic approach to measurement of spatial inequality - Walsh, J.A.; O'Kelly, M.E. (Economic & Social Studies, 1979)
In this paper we present some quantitative indices for measuring and comparing levels of inequality in discrete spatial distributions. The indices presented are based on the Kullback Information Measure which we consider to be the most general. In the final section of the paper the indices are applied to measure inequality in per capita income and certain categories of employment distribution in Ireland. The results indicate a tendency towards increasing uniformity in the spatial distribution of per capita incomes and employment opportunities.
Keywords: Employment - Ireland; Sociology